Festivals in Asia: patronage, play, and piety - Teeuwen, Mark (Religion, 2023)
This introductory article argues, on the basis of case studies in the thematic issue, that the interplay of patronage, play, and piety provides us with a productive framework for the study of Asian festivals. We focus on the frictions inherent in festivals that include multiple actors, agendas, and precedents, and that are subject to constant change. The three concepts of patronage, play, and piety serve as tools to make sense of these frictions and their manifestation in concrete performances. All articles in this issue look at a particular festival (or set of festivals) as sites where the interests of patronage, play, and piety are negotiated in dynamic ways. We use the findings from these articles to theorise on each of these aspects. Our aim is to propose a conceptual framework that, we argue, can be usefully employed to study festivals in and outside of this large and heterogeneous region.